EDTA and α‐tocopherol improve the chemical stability of astaxanthin loaded into nanostructured lipid carriers. Issue 8 (1st July 2014) - Tamjidi, Fardin; Shahedi, Mohammad; Varshosaz, Jaleh; Nasirpour, Ali
<x xml:space="preserve">Abstract</x> Nanostructured lipid carriers (NLC) as a promising delivery system have specific advantages over other nanocarriers for food applications. This study was aimed to evaluate the effect of different antioxidants on physical and chemical stability of NLC containing astaxanthin, a hydrophobic nutraceutical. Antioxidants (EDTA, ascorbic acid, α‐tocopherol, coenzyme Q10) were added to aqueous and/or lipid phases. Tween 80 and lecithin were utilized as stabilizers; NLC formulations were produced by melt emulsification‐sonication technique, and then stored at 35°C for 15 days. Except formulations with high levels of EDTA or ascorbic acid, others yielded small nanoparticles (Z‐average ≈ 94 nm) which were stable to growth during storage. Of these antioxidants, only EDTA and α‐tocopherol increased the stability of astaxanthin without causing physical instability, and EDTA was more efficient. The utilization of α‐tocopherol and EDTA in combination was more effective than using them individually. Storage temperature and artificial light had significant effects on the stability of astaxanthin in NLC. These results provide useful information for choosing antioxidants and storage conditions to further protection of nutraceuticals within NLC. Practical applications: Fortification of aqueous‐based foods with carotenoids is greatly restricted owing to their poor water‐solubility, chemical instability, and low bioavailability. NLC immobilize the encapsulated compounds effectively, and can improve their stability and bioavailability in aqueous‐based foods. However, pro‐oxidants can still decrease the chemical stability of NLC. Different antioxidants were employed to further increase the chemical stability of astaxanthin‐loaded NLC. It was found that degradation of astaxanthin in NLC could be significantly reduced by utilizing proper chelators and free radical scavengers. But, higher temperatures and light could still decrease the stability of astaxanthin. These results provide strong evidences for utilizing metal chelators and free radical scavengers in carotenoids‐loaded NLC, and for storing commercial foods and beverages fortified with these nanoparticles at low temperature and darkness. <inline-graphic xlink:href="ark:/27927/pghxt54144" content-type="ejlt201300509-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> Degradation profiles of astaxanthin in astaxanthin‐NLC containing 100 ppm EDTA in aqueous phase and/or different concentrations of α‐tocopherol (in lipid phase) after production (on 0th day) and during storage at 35°C (n = 3).